The Impact Of Shariah Approved Companies On The Relationship Between Corporate Governance Structure And Voluntary Disclosure Of Interim Financial Reporting In Jordan - Ala’ Hussein ALBAWWAT,; Mohamad Yazis Ali Basah (Human resaource Management Academy Society, 2024)
This study examines the impact of shariah approved companies on the relationship between corporate governance structure and voluntary disclosure of half-yearly reports in Jordan, focusing on variables that affect voluntary disclosure of the ASE Jordanian listed companies. The dynamic panel system GMM estimation was employed on the data from 72 selected ASE listed companies for the period of 2009-2013, and the results show that a substantial level of voluntary disclosure is demonstrated in high level corporate governance awareness and implementation in Jordan. Specifically, the factors of board compensation, number of shareholders, government ownership and Shariah approved company significantly impact voluntary disclosure. In addition, this study shown that the effect imparted by the presence of audit committee, board size, and block-holder ownership on the level of voluntary disclosure appear to be greater among the Shariah approved companies. Aside from that, voluntary disclosure in the half-yearly reports has potential impact on market capitalization. The findings may provide some implications for research regarding the voluntary disclosure and Shariah approved companies of financial reporting in Jordan.